Magnetic Resonance Imaging Evaluation of Spinal Infections - Vulchi Ranjith Kumar; Rama Krishna Rao Baru (Asian Journal of Medical Radiological Research, 2020)
Background: The advantage of Magnetic resonance imaging include multiplanar capabilities and soft-tissue contrast resolution, which is superior to that of CT. Magnetic resonance (MR) imaging is a powerful diagnostic tool that can be used to help evaluate spinal infection and to help distinguish between an infection and other clinical conditions. Aim of the current study is to evaluate various spectrum and types of spinal infections, and discussing the role of MRI in diagnosing them and their characterization. Subjects & Methods: This Hospital-based prospective study consists 30 patients with clinically suspected spinal infections and chronic non-resolving low backache referred to the department of Radiodiagnosis in a period of 2 years. Investigations include Complete blood count, ESR, sputum analysis for acid-fast bacilli and MRI of the spine. Results: 20 cases involved the lumbar spine, of which 12 were tubercular, seven were pyogenic, and one case was actinomycosis. In total 21 tubercular cases, 12 cases involved lumbar spine (57%), 8 cases affects the thoracic spine (38%), and 1 case involves the cervical spine (P = 0.562). the incidence of spondylodiscitis is common overall in the lumbar spine. 23.8% of tubercular and 12.5 %of pyogenic cases involved more than two vertebrae. T1 hypointensity is seen in 18 cases of tuberculosis (85%), 8 cases of pyogenic (75%), and 1 case of actinomycosis (100%) (P = 0.801). 4 cases showed preservation of disc height, among which three are tubercular (75%), and 1 was actinomycosis (25%). 85 % of tubercular and 100% of pyogenic cases showed disc narrowing. 81 % of tubercular and 100 % of pyogenic cases showed disc hyperintensity. Nine cases of tuberculosis (42.9%) and 3 cases of pyogenic (37.5 %) showed epidural abscess. 26 cases showed para vertebral extension of which 18 were tubercular (69.2 %), 7 were pyogenic (26.9 %) and 1 was actinomycosis (3.8 %). 94% of tubercular and 42 % of pyogenic abscesses showed a well-defined para spinal signal in cases of paraspinal extension. 15 of the 18(83%) tuberculosis, 3 of the 7 (42%)cases of pyogenic, and 1 case of actinomycosis showed subligamentous spread along more than three vertebrae. Heterogenous enhancement was noted in 12 of the 15 (80%) tubercular cases, 1 of the 3 (33%) pyogenic cases, and 1(100%) actinomycosis case. 71% tubercular cases and 2 of 8 (25%) cases showed predominant anterior 2/3rd involvement. Grade III or more (>50%) vertebral destruction was seen in 16 tubercular (76%) and 2 pyogenic cases (25%). Six cases showed skip lesions of which 5were tubercular and 1 was pyogenic. 5 of the 21 (23.8%) tubercular and 1 of the 8 (12.5%) pyogenic cases showed skip lesions. Conclusion: Awareness of atypical MR imaging at early infectious spondylitis is important to avoid diagnostic delay and unnecessary other diagnostic procedures. Several non-infectious conditions may simulate the spinal infections. Hence It is helpful to be aware of these diseases and their MR imaging features. With these points in mind, MR imaging can be very beneficial to patients with spinal infection.